An analysis of knowledge, attitudes, practice and influencing factors for tuberculosis prevention and control among Hainan University students - Xie, Huifang; Wang, Wencai; Chen, Xuan; Huang, Dan; Yu, Qiuyue; Luo, Liumei (Frontiers in Public Health, 2025)
ObjectiveTo assess the current status of knowledge, attitude, and practice pertaining to tuberculosis prevention among college students in Hainan Province, China, and to identify influential factors. The findings of this study are intended to provide valuable insights for the development and implementation of effective health education programs aimed at tuberculosis prevention and control.MethodsA convenient sampling method was employed to conduct a questionnaire-based survey among college students at a university in Hainan Province using the Wenjuanxing platform from January to February 2023. The survey evaluated students’ general information and their knowledge, attitude, and practice regarding tuberculosis prevention and control. The scores of correct knowledge, attitude, and practice were compared based on students’ demographic characteristics. Multiple linear regression analysis was used to determine the influencing factors of students’ knowledge, attitude, and practice related to tuberculosis prevention and control.ResultsA total of 280 questionnaires were distributed, of which 265 valid responses were collected, resulting in a valid response rate of 94.6%. The study found that medical students exhibited higher levels of correct knowledge, attitude, and practice compared to non-medical students (5.92 vs. 5.17, 3.17 vs. 2.57, 3.48 vs. 2.78, respectively). Moreover, students who had received tuberculosis education had higher correct scores compared to those who had not (5.92 vs. 5.31, 3.08 vs. 2.65, 3.31 vs. 2.93, respectively). Additionally, students in higher grades demonstrated higher scores in attitude. Three variables were found to influence students’ knowledge, attitude, and practice related to tuberculosis prevention and control, accounting for 33.4% of the explanatory power (F = 11.930; p < 0.001). Grade, major, and whether they had received tuberculosis education included.ConclusionThe study revealed a generally poor level of awareness among college students regarding tuberculosis prevention and control knowledge and the importance of regular physical exercise. Grade, major, and whether students had received tuberculosis education were identified as influencing factors. These factors should be prioritized in university tuberculosis education programs. Moreover, the implementation of physical education in schools is crucial in promoting students’ health.